Luminescence and tenebrescence in aluminate sodalites and related materials - Tomele, Madara (My University, 2024)
Research into inorganic luminescent and tenebrescent (colour-changing) materials with tunable properties has gained increasing attention in recent years. Hackmanite Na8Al6Si6O24(Cl,S)2 is a member of the sodalite group that possesses both luminescent and tenebrescent properties. Various studies exchanging framework and extra-framework ions have been performed in order tune optical properties of hackmanites. It has been observed that by expanding the cage-like structure of the framework F-centers, point defects also known as colour centers which are responsible for the colour change in inorganic solids, absorb longer wavelengths of light. It is also known that exchanging extra-framework cations and anions can affect the luminescent and tenebrescent properties of these materials. Based on these observations it can be concluded that by synthesizing a sodalite with a larger framework by, for example, exchanging Si atoms for Al and using aluminate sodalites as the base material as well as using various dopants, new compounds with different luminescence and tenebrescence properties could be produced. Samples containing Ca8Al12O24S2 modified using various dopants were synthesized and their luminescence and tenebrescence properties were analyzed. First S2- ions were exchanged with Cl- ions, which are necessary for the tenebrescence mechanism, in various proportions. Next the Ca2+ ions were exchanged with Li+, Na+, K+ and Rb+ ions. The aim of this project was to analyze the effects of different ions on the optical properties of these materials. Sample with the S/Cl ratio of S1.4Cl1.2 had some of the highest photo- and thermoluminescence intensity of all calcium aluminate sodalite containing samples. All alkali metal dopants increased the photoluminescence emission intensity of the base material, with M1.2Ca7.4 (M – alkali metal) being the ratio with the highest intensity in all doped samples. Tenebrescence after irradiation with 254 nm UV was not observed in any of the samples, however, a sample containing only LiAlO2 phase showed a clear colour change after irradiation with X-rays from the X-ray fluorescence measurement.
Keywords: sodalites, luminescence, tenebrescence, photochromism